Masterpiece : iconic houses by Great Contemporary Architects - Browne, Beth (Victoria, Australia : The Images Publishing Group Pty Ltd., 2012)
Every great architect has an original vision. The ability of master architects to see the big picture, to create inclusive, responsive designs that embrace building, site, and interiors with subtlety and style, leads to their work gaining widespread praise and international acclaim. Their talent and ambition, along with an unfaltering attention to detail and flair for fusing art and architecture, combine to produce houses of unparalleled style and comfort. Masterpiece: Iconic Houses by Great Contemporary Architects presents an up-to-the-minute collection of residential work from these much-lauded practitioners, proving that architecture can always be re-imagined. This invaluable new compendium of spectacular houses designed by architecture's brightest stars also provides unique insights into their personal design philosophies. Stunning architectural photography of each house is supplemented with detailed descriptions, plans, sections, and sketches, revealing the mastery behind each design. Project locations range from the USA to France, from Italy to Dubai, and from Hong Kong to Spain.
Keywords: ARCHITECT-DESIGNED HOUSES -- HISTORY-- 20TH CENTURY -- PICTORIAL WORKS